Enhancement of elastin expression by transdermal administration of sialidase isozyme Neu2 - Akira Minami (Nature Portfolio, 2021)
Abstract Reduction of elastin in the skin causes various skin diseases as well as wrinkles and sagging with aging. Sialidase is a hydrolase that cleaves a sialic acid residue from sialoglycoconjugate. Cleavage of sialic acid from microfibrils by the sialidase isozyme Neu1 facilitates elastic fiber assembly. In the present study, we showed that a lower layer of the dermis and muscle showed relatively intense sialidase activity. The sialidase activity in the skin decreased with aging. Choline and geranate (CAGE), one of the ionic liquids, can deliver the sialidase subcutaneously while maintaining the enzymatic activity. The elastin level in the dermis was increased by applying sialidase from Arthrobacter ureafaciens (AUSA) with CAGE on the skin for 5 days in rats and senescence-accelerated mice prone 1 and 8. Sialidase activity in the dermis was considered to be mainly due to Neu2 based on the expression level of sialidase isozyme mRNA. Transdermal administration of Neu2 with CAGE also increased the level of elastin in the dermis. Therefore, not only Neu1 but also Neu2 would be involved in elastic fiber assembly. Transdermal administration of sialidase is expected to be useful for improvement of wrinkles and skin disorders due to the loss of elastic fibers.